Keterlibatan Badan Penanggulangan Bencana Aceh (BPBA) Dalam Kesiapsiagaan Bencana Terhadap Disabilitas - Afalia, Yola; Sabirin, Sabirin; Saputra, Hijrah (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2025)
This study examines the involvement of the Aceh Disaster Management Agency (BPBA) in disaster preparedness for persons with disabilities, who are often overlooked in disaster management programs. The objective of this research is to analyze BPBA's efforts in preparing and protecting individuals with disabilities before disasters occur. The methodology employed is a qualitative approach, utilizing data collection through interviews and observations with informants including the Head of the BPBA Preparedness Division, Chairman of the Disaster Risk Reduction Forum (PRB), PRB members, Support Teachers, and Persons with Disabilities. The findings indicate that BPBA has undertaken various initiatives to enhance disaster preparedness for persons with disabilities through partnerships. However, this study also recommends that BPBA establish a dedicated disability services unit to address the needs of individuals with disabilities.